Biofuels, production, application and development - Scragg, A. H. (Alan H.), 1943- (CABI, 2009)
Explores the production of biofuels as alternatives to fossil fuels, focusing on the technological issues. This textbook considers each type of biofuel in production, covering the benefits and problems with production and use and the potential for biological material to provide sufficient energy for the world's population.